Factors that influence breast cancer screening among women of reproductive age in the Nandom Municipality, Ghana - Margaret Mary Wuur; Dillys Adomakoa Duodu; Elvis Enowbeyang Tarkang (BMC, 2022)
Abstract Background In Ghana, breast cancer is a major public health concern and the most common type of cancer among women in terms of mortality and incidence. This study determined the factors influencing breast cancer screening among women of reproductive age in Nandom Municipality, Ghana using the Health Belief Model as the conceptual model. Methods The study was cross-sectional in design. A pretested structured questionnaire was administered to 243 womens of reproductive age in the Nandom Municipality. Descriptive and inferential statistics were performed using STATA version 16 at a 0.05 level of significance. Results The uptake of breast cancer screening was 51.9%. Respondents who had a tertiary level of education were less likely to be screened for breast cancer [AOR = 0.10 (95% CI = 0.02-0.54); p = 0.008]. Respondents who perceived high susceptibility to breast cancer were more likely to get screened [AOR = 1.97 (95% CI = 1.12-3.47), p = 0.019]. Respondents who perceived the high severity of breast cancer were more likely to be screened for breast cancer [AOR = 4.55 (95% CI = 1.32-15.76), p = 0.017]. Also, respondents who perceived high barriers to breast cancer screening were more likely to be screened for breast cancer [AOR = 0.15(95% CI = 1.42-4.22), p < 0.001]. Conclusion The uptake of screening among women of reproductive age in the Nandom Municipality is low. Health promotion interventions to improve breast cancer screening should target women with a tertiary level of education and should focus on heightening the perceived threat of breast cancer and minimizing barriers to breast cancer screening.